2018
DOI: 10.4103/jrms.jrms_1009_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of salivary testosterone levels in different phases of bipolar I disorder and control group

Abstract: Background:Testosterone is considered as a primary sex hormone, also known as an important anabolic steroid, that may involve in various mental disorders such as bipolar I disorder (BID). The goal of this study was to compare the testosterone salivary levels between different phases of BID and its association with the clinical features of BID.Materials and Methods:In a case–control study, 15 patients in the mania phase, 10 patients in the depression phase, and 16 in the euthymia phase were selected as patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The depressive and manic phases appear to be associated with different gonadal hormone profiles. Previous studies have found that testosterone levels are higher during manic episodes and lower during depressive episodes in contrast to controls [ 41 44 ]. The findings of our study are similar.…”
Section: Discussionmentioning
confidence: 99%
“…The depressive and manic phases appear to be associated with different gonadal hormone profiles. Previous studies have found that testosterone levels are higher during manic episodes and lower during depressive episodes in contrast to controls [ 41 44 ]. The findings of our study are similar.…”
Section: Discussionmentioning
confidence: 99%
“…At follow‐up, elevated baseline testosterone levels predicted suicide attempts such that a 10 ng/dL increase in testosterone translated to a 16.9‐times increased probability of suicide attempt. While it should be noted that one study found no significant differences in salivary testosterone levels either between BD type I patients and healthy controls or between euthymic, depressed, and manic BD patients (Mousavizadegan & Maroufi, 2018), there are reports of hypomania (Freinhar & Alvarez, 1985) and mania (Elboga & Sayiner, 2018) induced by androgen administration, as well as homicide after a man with BD was administered testosterone for hypogonadism (Sher & Landers, 2014). In a case with comorbid Klinefelter syndrome, however, testosterone therapy has been reported to effectively treat a pattern of frequent manic episodes refractory to treatment with mood stabilizers and second‐generation antipsychotics (Kawahara et al, 2015).…”
Section: Resultsmentioning
confidence: 97%
“…At follow-up, elevated baseline testosterone levels predicted suicide attempts such that a 10 ng/dl increase in testosterone translated to a 16.9-times increased probability of suicide attempt. While it should be noted that one study found no significant differences in salivary testosterone levels either between BD-I patients and healthy controls or between euthymic, depressed, and manic BD patients (Mousavizadegan and Maroufi, 2018), there are reports of hypomania (Freinhar and Alvarez, 1985) and mania (Elboga and Sayiner, 2018) induced by androgen administration, as well as homicide after a man with BD was administered testosterone for hypogonadism (Sher and Landers, 2014). In a case with comorbid Klinefelter syndrome, however, testosterone therapy has been reported to effectively treat a pattern of frequent manic episodes refractory to treatment with mood stabilizers and second-generation antipsychotics (Kawahara et al, 2015).…”
Section: Domestication Features In Bdmentioning
confidence: 97%